Classical solutions for the Vlasov–Poisson system with damping term. Issue 5 (4th April 2019) - Xiao, Meixia; Zhang, Xianwen
ABSTRACT: We investigate global existence of classical solution to the three dimensional Vlasov–Poisson system with radiation dampingD f [ 3 ] ( t ) . We prove that a small perturbation of initial datum for a global classical solution verifying certain decay conditions also launches a global solution which has sharp decay. In addition, we prove that a quasineutral initial datum launches a global classical solution.